Aggregated Markov models of a heterogeneous population of photovoltaic panels - Peruffo, A; Guiu, E; Panciatici, P; Abate, A (Springer, Cham, 2017)
We present a new framework for aggregated quantitative modelling of a heterogeneous population of photovoltaic panels. We are interested in the behaviour of photovoltaic panels as electric power sources, and in an aggregated model that can capture how such a population behaves when connected to the power grid. After an initial analysis of the characteristics and behaviour of a single device, we propose two Markov chain models for the aggregation of a heterogeneous population of such devices. We study the dynamical behaviours of the aggregated models, embedded within the dynamics of the grid frequency. A simulation study shows the effectiveness of the aggregated models when compared to the physical system, and leads to conclude that population heterogeneity is a desirable feature for the overall system dynamics.